The Remote Control of Gas Holders within British Gas Southern - C J Hales (Measurement + Control, 1987)
This paper was originally presented at a meeting of the Wessex Section of the Institute of Measurement and Control on 28 March 1985, and was awarded the BIMCAM Ardley Award for the best paper presented to a Local Section in the 1984/5 Session.